Pregnancy-Triggered Severe Lupus Nephritis with Pleural Effusion: A Case Report - Zaki Mahmudi Dasril; Deka Viotra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus (SLE), characterized by kidney inflammation. Pregnancy can trigger or exacerbate LN due to hormonal shifts and altered immune responses. This case highlights the challenges in diagnosing and managing pregnancy-associated LN. Case presentation: A 27-year-old woman presented with anasarca, malar rash, shortness of breath, and foamy urine during her first pregnancy. She had a history of SLE with previous symptoms limited to skin and joint involvement. Investigations revealed nephrotic-range proteinuria, hematuria, elevated creatinine, and positive anti-nuclear antibodies (ANA). Renal biopsy confirmed Class IV lupus nephritis. She was diagnosed with pregnancy-triggered severe LN with nephrotic syndrome, pleural effusion, and a hypercoagulable state. Treatment included high-dose corticosteroids and mycophenolate mofetil, with close monitoring of both maternal and fetal health. Conclusion: This case underscores the importance of recognizing and promptly managing LN in pregnancy. Early diagnosis, multidisciplinary care, and individualized treatment are crucial to optimize maternal and fetal outcomes.